An Initial Study of Cyber Security for Web Services in Malaysian Organizations - Hamid Ali, Firkhan Ali Bin; M. Sukri, M. Khairul Amin; M. Yusof, M. Azahari; Jali, Mohd Zalisham; Nordin, Moh Norazmi; Surip, Miswan (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In the recent and next years, Malaysian enterprises have seen an increase in the development of information technology (IT). This is a result of the Malaysian government actively promoting IT usage throughout all companies in Malaysia, whether they are in the public or private sectors. Utilizing IT including web services will increase an organization’s production and quality. Therefore, they require a well-planned implementation of the IT infrastructure and tools. Using web services will ensure that its operations are successful in supporting long-term business ambitions. Besides that, the cyber security play important role to ensure that the web services and IT infrastructures execute well along the organization’s business successful. So, is these digital environments in Malaysian organizations safe it is not a Malaysian IT culture and didn’t have enough and tough knowledge of cyber security. However, how to promote cyber security to Malaysian organizations for web services? So, promotion can be done by using the web services itself by putting more knowledge and study on the secure usage of IT facilities in Malaysian organizations.